2010
DOI: 10.1584/jpestics.g09-68
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic bioavailability of 14C-heptachlor to several plant species

Abstract: 14C-heptachlor for 72 hr. The levels and nature of 14 C-residues in roots and shoots of treated plants were determined to estimate the values of the root concentration factor (RCF) and the transpiration stream concentration factor (TSCF). RCF and TSCF values ranged from 126 (corn) to 4086 (lettuce) and 0.052 (Chinese cabbage) to 0.494 (zucchini), respectively. In pumpkin and zucchini, unmetabolized heptachlor itself was translocated from the root to the shoot via a transpiration stream and no further extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Radiolabeled heptachlor ( [4,5,6,7,[8][9][10][11][12][13][14] C]heptachlor, specific radioactivity 11.5 MBq/mg, radiochemical purity 97.9%), prepared by custom synthesis, was purchased from Moravek Biochemicals (Brea, CA). 9) Non-radiolabeled heptachlor and 1-hydroxychlordene were purchased from Wako Pure Chemical Industries (Osaka, Japan), and cis-and trans-heptachlor epoxides were from Hayashi Pure Chemical Industries (Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Radiolabeled heptachlor ( [4,5,6,7,[8][9][10][11][12][13][14] C]heptachlor, specific radioactivity 11.5 MBq/mg, radiochemical purity 97.9%), prepared by custom synthesis, was purchased from Moravek Biochemicals (Brea, CA). 9) Non-radiolabeled heptachlor and 1-hydroxychlordene were purchased from Wako Pure Chemical Industries (Osaka, Japan), and cis-and trans-heptachlor epoxides were from Hayashi Pure Chemical Industries (Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] However, there is little information regarding the uptake of heptachlor by crops after soil treatment. We previously reported the root uptake of 14 C-heptachlor to various plants under hydroponic cultivation 4) and indicated that the 14 C-concentrations in shoots of wheat, cucumber, tomato, and zucchini were higher than those of other plant seedlings after exposed via the hydroponic solution. In addition, we reported the degradation of 14 C-heptachlor in Japanese soils 5) and found that the concentration ratio of heptachlor and its degradation products remained constant in the soil three to four months after the application of 14 C-heptachlor.…”
mentioning
confidence: 97%
“…The pre-cultivation method of treating the test plant was described in the previous report. 4) The numbers of pre-cultivation days from sowing of the test plants used are 19 days (tomato) and 12 days (zucchini).…”
mentioning
confidence: 99%
See 2 more Smart Citations